Enhancing Plant Growth and Photosynthesis with Biofertilizers from Sewage Treatment - Ferreira, Elisa Teófilo [UNESP]; Caetano, Lucas Eduardo Santana [UNESP]; Candido, Júlia Messias Bressan [UNESP]; Cechin, Inês [UNESP]; da Silva, Gustavo Henrique Ribeiro [UNESP] (MDPI, 2025)
The increasing production of sanitary sewage, driven by urban population growth and increased collection and treatment, is a significant concern due to its potential to cause environmental degradation. Sanitary sewage treatment offers an opportunity to recycle nutrients and water, which can be used as fertilizers in agriculture. This study aimed to evaluate bioproducts derived from sanitary sewage treatment as biofertilizers for sunflower plants. Different concentrations of dried microalgae cultivated in sewage and biosolids from anaerobic sewage treatment were added to plants grown in plastic pots filled with vermiculite with a 20% Long Ashton (LA) nutrient solution. Additionally, we used either pure reclaimed water or a combination of reclaimed water with the LA. All biofertilizers increased the dry matter of the shoot. Transpiration and stomatal conductance were little affected. Photosynthesis and instantaneous water use efficiency were increased while the CO2 concentration in the substomatal cavity was decreased. The results demonstrate that the biofertilizers improved plant growth and photosynthesis due to their high nutrient availability. This study underscores the potential of these biofertilizers to promote crop growth and photosynthesis, providing an alternative to chemical fertilizers while conserving potable water. Such innovations contribute to sustainable agriculture, particularly benefiting small-scale growers facing the challenges of climate change.
Keywords: circular economy; food production; nutrients; photosynthesis; sunflower